Factors influencing consumer attitudes towards web series content marketing - Santosa, Allicia Deana; Alversia, Yeshika; Rahmawati, Mira (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Content marketing is growing and nowadays many companies and brands create short movies/series as their content marketing strategies and this practice is becoming a trend. Unfortunately, there’s a lack of research on short movies/series as a content marketing tool since it is a new trend, previous research for a product/brand in a movie is research on product placement. Thus to fill in the research gap, the present study examines the factors influencing consumer attitudes towards the short movie/series created by a company to shed the light on short movies/series as content marketing. The population in this study is comprised of social media users who have watched short movies/series created by a brand as an ad. 225 respondents were selected using a non-probability sampling and main data were collected through a self-administered online questionnaire which was distributed for Indonesian social media users. Structural equation modeling has been used to analyze the data. The results indicate that narrative enjoyment and attitudes toward the actor positively affect attitudes toward the short movie/series. Persuasion awareness negatively influences attitudes toward the short movie/series and attitudes toward the brand. Attitudes toward the short movie/series positively affect attitudes toward the brand. These findings are expected to contribute to content marketing literature and are useful to managers, marketers, and business people utilizing online media.